Impacts of climate-smart crop varieties and livestock breeds on the food security of smallholder farmers in Kenya - Radeny, Maren A.O.; Rao, E.J.O.; Ogada, Maurice Juma; Recha, John W.M.; Solomon, Dawit (Springer, 2022)
This paper analyses the impact of climate-smart agriculture (CSA) technologies on household dietary diversity and food insufciency as indicators of food and nutrition security in Kenya. Using a combination of Propensity Score Matching and endogenous treatment efect approaches, we found that adoption of stress-tolerant varieties of several crops (such as bean, pigeon pea, cowpea, maize and sorghum) improved household dietary diversity score by 40% and reduced food insufciency by 75%. Adoption of improved and resilient livestock breeds (including Red Maasai sheep and Galla goats) improved household dietary diversity by 38% while reducing household food insufciency by 90%. We also found that stress-tolerant crop varieties were more efective in improving food security outcomes among households with large landholdings and with more educated and younger to middle-age heads. Efects of resilient livestock breeds on household food security were much stronger for households with large landholdings and with young and/or much older heads that have low levels of education. Given the large, demonstrated benefts from the use of the CSA technologies, policies and programs aimed at their promotion should apply appropriate targeting to ensure wider uptake of the technologies and maximum returns on investment.